La nozione di moto nelle concettualizzazioni degli stati di sonno, sogno, meditazione e ipnosi nella lingua italiana - Kuncy-Zając, Anna (Neophilologica, 2011)
The aim of this article is to analyze the notion of movement in the conceptualizations of some altered states of consciousness, such as: sleeping (sonno), dreaming (sogno), meditation (meditazione) and hypnosis (ipnosi) in the Italian language. The research presented is based on the following theories: thematic proto-roles by D. Dowty (1991) and Kinesthetic Image Schemas by G. L akoff (1987), which are a basis for Idealized Cognitive Models (G. Lakoff, 1987). In order to carry out the analysis I took into consideration: the proto-role of the experiencer, the existence or lack of the boundaries in the visions of the states examined and the directions of the metaphoric movement of the state and of its experiencer, both during the very state and as a shift in the consciousness level occurs. I also verified the correlations between these elements and the part of the source — path — goal image schema emphasized in each conceptualization. The conclusions of my study indicate the similarities and differences in the vision of movement in the analyzed concepts.